Evaluasi Kualitas Layanan Program Studi Administrasi Bisnis Polimdo menggunakan Importance-Performance Analysis - Kaparang, Gratia Natrina; Samehe, Januar Valentino; Lendo, Fresi Beatrix; Tumengkol, Inka Marry Steviarty (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
The purpose of this research is to measure the suitability and gaps that occur in the expectations and reality of students studying in the Business Administration Study Program. To measure the extent to which students' hopes come true when carrying out lecture activities in the Business Administration Study Program. The focus of this research is to raise the problem that the Polimdo Business Administration Study Program is always improving and wants to develop services, so that every year it conducts research for students about the quality of services in the Business Administration Study Program. To measure service quality from the Business Administration Study Program, the SERVQUAL indicator is used which refers to the theory of Parasuraman, et al (1985), namely tangibles, responsiveness, reliability, assurance and empathy. Analysis was carried out quantitatively using the Importance-Performance Analysis method (Martilla James, 1977). Based on the results obtained, it was concluded that several air conditioners in the classroom needed to be repaired to provide comfort for students, teaching materials needed to be published on the study program's official website to make it easier to access teaching materials, and there was a need for counseling services between students and guardian lecturers.